(untitled) (Ameghiniana, 2013)
The finding of resting trails of trilobites in Campanario Formation in the province of Salta is the first mention of any fossil but Scolithus, in the Cambrian of Northwestern Argentina. The traces are identified as belonging to Rusophycus bilobatus (Vanuxem). Some other trilobites traces as Roualtia lyelli (Roualt ) and Cruziana furcifera D’Orbigny of Ordovician age, are studied and compared.